Eco-friendly management approach to control cabbage flea beetle in Jashore region of Bangladesh (Progressive Agriculture, 2020)
The experiment was conducted during rabi season 2018-19 and 2019-20 at Regional Agricultural Research Station Jashore to develop a bio-rational based sustainable management approach to control flea beetle of cabbage. The experiment was laid out in a randomized complete block design with three dispersed replications. Cabbage seedlings were transplanted on 10th November 2018 and 11th November 2019, respectively. The experiment was five different treatments with one control treatment viz. T1 = White color sticky trap + Matrin (Biotrine 0.5% @ 1ml/L of water) @ 1ml/L of water, T2 = Spraying of Antario @1.0 ml/L of water, T3 = Alternate spraying of fizimite and Antario @ 1ml/L of water, T4 = Spraying of Bio-clean (D-Lemonine 5% SL) + application of recharge @ 3gm/L of water, T5 = Spraying with Nitro 505EC (Chlorpyriphos + Cypermethrin) @ 2.0 ml/L of water and T6 = Untreated control. The whole plant was thoroughly covered by spray emulsion. The lowest number of flea beetle (14.59 in 2018-19 and 10.33 in 2019-20) was found in the treatment T5 (Spraying with Nitro 505EC (Chlorpyriphos + Cypermethrin) @ 2.0 ml/L of water) and highest (35.76 in 2018-19 and 42.53 in 2019-20) in control (T6) treatment. The lowest percent of head infestation of cabbage was also recorded in T5 treatment (14.03% in 2018-19 and 5.10% in 2019-20) and the highest in T6 treatment (27.61% in 2018-19 and 23.69% in 2019-20). The highest yield (33.40 t/ha in 2018-19 and 32.49 t/ha in 2019-20) was recorded from T5 treatment and the lowest (26.87 t/ha in 2018-19 and 24.78 t/ha in 2019-20) in control (T6) treatment in both the year. On an average, 16.55-20.33 flea beetle were captured in yellow sticky trap per week in both the year. The highest gross margin (438466 Tk.//ha in 2018-19 and 262366 Tk.//ha in 2019-20) was also observed in the T5 treatment in both the year and the lowest (342916 Tk.//ha in 2018-19 and 187666 Tk.//ha in 2019-20) in untreated control (T6) treatment. Finally, the results revealed that the treatment T5 was more profitable compared to other approaches as well as the highest crop yield with marginal benefit cost ratio.Progressive Agriculture 31 (2): 68-73, 2020